2021
DOI: 10.1111/jsr.13305
|View full text |Cite
|
Sign up to set email alerts
|

Acute and cumulative effects of scheduling on aircrew fatigue in ultra‐short‐haul operations

Abstract: Fatigue is a major cause of accidents in transport work, including aviation, according to the National Transportation Safety Board (NTSB, 1999). Because fatigue-related safety is linked to scheduling practice, authorities attempt to prevent fatigue through flight time limitations. The European Aviation Safety Agency (EASA) identifies night flying, early morning starts, long flight duty periods (>13 h during daytime) and a high level of sectors as scheduling characteristics contributing to aircrew fatigue (Comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 26 publications
0
9
0
5
Order By: Relevance
“…Others have also demonstrated that fatigue ratings are higher during early starts compared with later morning starts (Åkerstedt et al, 2021;Bourgeois-Bougrine et al, 2003;Flynn-Evans et al, 2018;Roach et al, 2012;Sallinen et al, 2017). This likely relates to later starts affording a longer sleep opportunity and to the circadian drive for alertness promoting waking during the biological day (Roach et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Others have also demonstrated that fatigue ratings are higher during early starts compared with later morning starts (Åkerstedt et al, 2021;Bourgeois-Bougrine et al, 2003;Flynn-Evans et al, 2018;Roach et al, 2012;Sallinen et al, 2017). This likely relates to later starts affording a longer sleep opportunity and to the circadian drive for alertness promoting waking during the biological day (Roach et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, later morning starts would have involved providing fatigue assessments at times that were likely during habitual wake periods. Åkerstedt et al ( 2021 ) found that sleep was the strongest predictor of fatigue over a 24‐period followed by duty type (including both early and late duties) and duty time. Although we did not find a statistically significant association between prior night's sleep duration and subsequent fatigue or performance, the amount of sleep that the pilots reported prior to early starts was 6.90 h, which is considered insufficient relative to consensus recommendations (Hirshkowitz et al, 2015 ; Watson et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies by Goffeng et al [ 43 ] and Åkerstedt et al [ 44 ] evaluated both pilots and flight attendants. The first of these investigations, a seven-day prospective cohort study confirmed higher number of consecutive workdays (≥days), short sleep, less rest time between flights, and high workload as risk factors for greater cardiovascular effort among pilots and flight attendants.…”
Section: Resultsmentioning
confidence: 99%